Theoretical Evaluation of Refractive Index in Binary Liquid Mixtures - Shipra Baluja; Nirmal Pandaya; Nikunj Kachhadia; Asif Solanki (E-Journal of Chemistry)
The density and refractive index (RI) for four binary liquid mixtures: diethyl malonate + dimethylformamide (DEM+DMF), diethyl malonate + Hexane (DEM+HEX), diethyl malonate + tetrahydrofuran (DEM+THF), diethyl malonate + 1,4-dioxane (DEM+DO) have been measured. The experimental values are compared with those calculated from Lorentz-Lorentz, Heller, Newton and Gladstone -Dale mixing rules.